Ozorków i jego mieszkańcy przełomu XIX i XX wieku na łamach „Rozwoju” - Pawlak, Magdalena (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
The article is designed to identify location, type and range of subjects information about Ozorków in “Rozwój” daily, published in Lodz in the years 1897–1914. Information about Ozorków published mostly in the so-called regular column (e.g. Kronika [The News], Z kraju [From the Land], Wiadomości zamiejscowe [Fledging posts]) and in separate articles. Occasionally, these texts published in columns appearing irregularly, but with the same title (e.g. Skrzynka do listów [Letter box], Kuryerek Resursy Rzemieślniczej [Craftsmen Club Resursa Courier]). The themes included in the articles were dominated by current problems the intercity communications (23% of the analyzed articles about the city) and issues related to the economy and industry of Ozorków (19%). Much less attention was dedicated to the local issues of social (11%), cultural and educational (together 11%) and questions of municipal engineering (5%). Against this background, there were quite a lot of articles on crime (9%) and events of the Revolution 1905–1907 (4%, but it should be noted that articles relating to these events were published within two years time only). Other articles about Ozorków (18%) were different thematically and they related inter alia: fires, accidents, military action in the first months of World War I and various curiosities.